Wi-Fi 7 in depth your guide to mastering Wi-Fi 7, the 802.11be protocol, and their deployment - Henry, Jerome (Addison-Wesley Professional, 2025)
Join wireless networking experts Jerome Henry, Brian Hart, Binita Gupta, and Malcolm Smith on this deep dive into Wi-Fi 7 and 802.11be. The authors share their practical experience to show you how to design and optimize your network to fully leverage Wi-Fi 7's new capabilities and deepen your understanding of the latest wireless networking advancements. You will learn the inner workings of Wi-Fi 7 PHY and MAC improvements like triggered uplink access, puncturing, rTWT, and SCS QC. You will explore the new possibilities of multi-link operations and learn why clients will come in five possible MLO modes that dramatically affect the expectations you can have for their performances. You'll gain real-world insights into protocol implementation and its effects on Wi-Fi cell design, roaming efficiency, and overall network performance.
Includes index
Keywords: Wireless LANs; Réseaux locaux sans fil